Pregnancy Related Acute Renal Failure in a Tertiary Care Hospital in Bangladesh (Journal of Medicine, 2012)
Background: Pregnancy related acute renal (PRARF) failure is more common in developing countries than developed country. Improved antenatal care and obstetric care reduce PRARF in developed country. In Bangladesh maternal mortality rate is 3.8/1000 population of which 25% account for acute renal failure. We try to find out cause, risk factor and out come of pregnancy related acute renal failure. Materials and Methods: A prospective observational study was done to observe the status of ARF in pregnancy in Nephrology Department of Dhaka Medical College during 2007-2008. All patients were undergone detail history, clinical examination and investigation and follow up during hospital stay. Data recorded in predesigned case record form. Statistical analysis was done with SPSS soft ware 12.5 package. All data presented as mean or percentage. The Chi square test or Fishers exact test was used to compare differences in the frequency of clinical manifestations among cases. P value